Non-foundational criticality? On the need for a process ontology of the psychosocial - Stenner, Paul H.D. (Outlines. Critical Practice Studies, 2007)
The articulation of critical dialects of psychology has typically involved a questioning of the foundational assumptions of the so-called mainstream. This has included critiques in the name of more adequate scientific foundations, but more recently these have been accompanied by critiques in the name of an absence of foundations altogether, and critiques that suggest a rethinking of the concept of foundation. These latter versions are usually influenced by the great 20th Century non-foundational philosophies of figures such as Bergson, Whitehead, Wittgenstein and Heidegger, or by related thinkers such as Deleuze, Serres, Luhmann, Butler and Stengers. In foregrounding themes of process and multiplicity such thinkers provide potent tools for critically rethinking psychological questions. Less positive has been a tendency amongst critical psychologists to polarise natural and social scientific issues and to associate the former with negative images (all that is static, mechanistic, essentialist and conservative). This can lead to a formulaic criticality in which arguments for nature are bad, and those for culture are good. Deconstruction comes to appear simply as an assertion of ‘the discursive construction of’ whatever phenomenon is under scrutiny. To counteract this trend, the proposed paper will discuss a process approach to ontology that welcomes contributions from the natural sciences as well as the humanities and social sciences.